Transvenous Obliteration Procedure in the Management of Parastomal Variceal Bleeding: A Case Report - Estorninho, João (2023)
Introduction: Parastomal variceal bleeding (PVB) is a recognized complication of ostomized patients in the presence of portal hypertension. However, since there are few reported cases, a therapeutic algorithm has not yet been established. Case Presentation: A 63-year-old man, who had undergone a definitive colostomy, recurrently presented to the emergency department hemorrhage of bright red blood from his colostomy bag, initially assumed to be caused by stoma trauma. Accordingly, temporary success on local approaches such as direct compression, silver nitrate application and suture ligation was achieved. However, bleeding recurred, requiring transfusion of red blood cell concentrate and hospitalization. The patient’s evaluation showed chronic liver disease with massive collateral circulation, particularly at the colostomy site. After a PVB with associated hypovolemic shock, the patient was submitted to a balloon-occluded retrograde transvenous obliteration (BRTO) procedure which stopped the bleeding successfully. The patient was subsequently proposed for a transjugular intrahepatic portosystemic shunt (TIPS) conjugated with percutaneous transhepatic obliteration (PTO). After an initial refusal by the patient, a new episode of self-limited PVB resulted in execution of the procedure. Four months later, in a routine consultation, the patient presented with grade II hepatic encephalopathy, successfully treated with medical therapy. After a 9-month follow-up, he remained clinically well and without further episodes of PVB or other adverse effects. Discussion: This report highlights the importance of a high index of suspicion when dealing with significant stomal hemorrhage. Portal hypertension as an etiology of this entity may compel to a specific approach to prevent recurrence of bleeding, including conjugation of endovascular procedures. The authors present a case of PVB, initially submitted to a variety of treatment options including BRTO, which was successfully addressed with conjugated treatment of TIPS and PTO.